Pengaruh Terapi Musik Klasik Mozart Dan Pemberian Aroma Terapi Lemon (Cytrus Limon) Dalam Menurunkan Tingkat Kecemasan Ibu Hamil - Melania Wahyuningsih; Rina Puji Rahayu; Anita Liliana (STIKes Payung Negeri Pekanbaru, 2022)
Anxiety is a feeling of deep worry. During pregnancy, physical and psychological changes can occur. The impact of anxiety on pregnant women can make pain during childbirth. Anxiety can be improved by giving Mozart classical music therapy and Lemon aromatherapy. The purpose of this study was to determine the administration of classical music therapy and lemon aromatherapy on the anxiety of pregnant women in the third trimester before delivery at the Karang Rejo Health Center, Tarakan City, North Kalimantan. Quasi-experimental research design, pre and post-test design without control. The research subjects were 32 people divided into 2, namely 16 music therapy and 16 aromatherapy respondents. incidental sampling technique. Sop research instrument, questionnaire. Statistical test paired t-test and independent t-test. The mean pre-test value of classical music therapy is 10.38(2.574), post-test 7.50(1.862) p-value 0.000. The mean value of lemon aromatherapy pre-test was 10.88(4.440), post-test 9.00(3.578) p-value 0.000. Independent t-test pre-test classical music therapy and lemon aromatherapy p-value 0.705, post-test p-value 0.151. The provision of classical music therapy and lemon aromatherapy were both effective in reducing the anxiety level of pregnant women in the third trimester before delivery at the Karang Rejo Health Center, Tarakan City, North Kalimantan.